INNOVATIVE FACTORS OF INCREASING YOUTH SOCIAL ACTIVITY IN MODERN CONDITIONS - Orif Shukurov (Scholar Express Journal, 2022)
This article talks about the innovative factors of increasing the social activity of young people in modern conditions. In recent years, in the process of reforms implemented in modern conditions, a number of works, studies, and scientific articles have been created on the problems of increasing the social activity of young people, which, in turn, contain the theoretical foundations of identifying existing problems and finding solutions to a certain extent
Keywords: Youth social activity; innovative initiative; reforms; society